IMPLEMENTASI MAHABBAH DALAM TRADISI ENDOG-ENDOGAN MASYARAKAT OSING DESA KEMIREN BANYUWANGI - Ahmad Imron Sutiyoso; Masykur Arif (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2024)
Indonesia is renowned for its rich and diverse cultural heritage, including unique traditions that reflect the values and beliefs of its people. One intriguing tradition is endog-endogan, practiced by the Osing people in Banyuwangi, which is associated with the celebration of Maulid Nabi Muhammad Saw. This tradition is not merely a customary celebration but holds deep spiritual significance as a manifestation of mahabbah a profound yearning to be close to Allah, full submission to His will, and a commitment to living a life of virtue, expressed through acts of kindness, love, and devotion to others. This study aims to address two issues: the Osing community’s understanding of mahabbah within the endog-endogan tradition and the implementation of mahabbah in this tradition. Employing a qualitative method with an ethnographic design, the research involves primary and secondary data from five informants, using techniques such as observation, interviews, and documentation. This research provides new insights into the endog-endogan tradition, detailing the Osing community’s understanding of mahabbah, which includes three aspects: its level, where the Osing's mahabbah is categorized as cinta bisa; its objects, including love for others, tradition, nature, and the Prophet Muhammad; and its nature, where the Osing’s mahabbah is identified as Hubb al-Hawa. The implementation involves five aspects: prioritizing kindness in every action, maintaining patience and forgiveness, building harmonious relationships, respecting and honoring others, and protecting the environment.